Podkhody kʺ zalivu Baĭkalʺ sostavleno po rabotamʺ 1915 g. Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago Okeana / Chertilʺ Kapitan mal. pl Vinogradovʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1914)
Relief shown by hachures. Depths shown by soundings and isolines.; Greenwich meridian.; "Masshtabʺ 1/8400 ili 1000 sazh. 7-ti futovoĭ mi︠e︡ry vʺ di︠u︡ĭmi︠e︡ po paralleli 53° 38'." = Scale 1/8400 or 1000 7-foot fathoms on average water in 1 inch on parallel 53° 38'.; Title translation: Approaches to Baikal Bay (залив Байкал) compiled from the work of 1915 of the Hydrographic Expedition of the Eastern Ocean Grayscale; 1:84,000